2017
DOI: 10.14198/cuid.2017.48.19
|View full text |Cite
|
Sign up to set email alerts
|

Cuidados de enfermería en la promoción del autocuidado de los pacientes con úlceras en las piernas: una revisión integradora

Abstract: Objective: To identify the evidence on nursing care in promoting self-care of patients with leg ulcers.Method: This is an integrative literature review whose search was conducted in databases: LILACS, MEDLINE, IBECS, CENTRAL, SCIELO and BDENF. Inclusion criteria were: articles in Portuguese, English and Spanish in its entirety and online, published between 2010 to 2015. Exclusion criteria were: articles repeated in different databases and systematic reviews. After reviewing the publications in full as the esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In fact, nursing through experimental studies in the area has shown that patients receiving care under a community care model that promotes social interaction, participation, empathy, peer support and empowerment of their condition have shown shorter healing times, having improved their quality of life, perceived social support, self-esteem, and decreased their pain 55,56 . Furthermore, nursing interventions that promote healthy lifestyles, self-care, physical activity and exercise have also shown positive results in VU healing rates among other psychosocial variables [57][58][59] .…”
Section: Association Of Psychosocial Factors With Vu Curingmentioning
confidence: 99%
“…In fact, nursing through experimental studies in the area has shown that patients receiving care under a community care model that promotes social interaction, participation, empathy, peer support and empowerment of their condition have shown shorter healing times, having improved their quality of life, perceived social support, self-esteem, and decreased their pain 55,56 . Furthermore, nursing interventions that promote healthy lifestyles, self-care, physical activity and exercise have also shown positive results in VU healing rates among other psychosocial variables [57][58][59] .…”
Section: Association Of Psychosocial Factors With Vu Curingmentioning
confidence: 99%
“…De hecho, Enfermería a través de estudios experimentales en el área ha evidenciado que los pacientes que reciben atención bajo un modelo de cuidado comunitario que promueve la interacción social, la participación, la empatía, el apoyo entre compañeros y el empoderamiento de su condición han evidenciado tiempos de cicatrización más cortos, mejora en la calidad de vida, soporte social percibido, autoestima y disminución del dolor 55,56 . Más aún, las intervenciones de enfermería que fomentan los estilos de vida saludable, el autocuidado, la actividad física y el ejercicio también han mostrado resultados positivos en las tasas de cicatrización de las UV entre otras variables psicosociales [57][58][59] .…”
Section: Asociación De Los Factores Psicosociales Con La Curación De ...unclassified